2020
DOI: 10.1055/s-0040-1718751
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Safety and Outcomes of Mucous Fistula Refeeding in Neonates

Abstract: Introduction The utility of mucous fistula refeeding (MFR) in neonates with short bowel syndrome is widely debated. Our purpose is to review MFR and outline methods, reported complications, and clinical outcomes (survival, weight gain, dependence on parenteral nutrition [PN], and time to enteral autonomy). Materials and Methods We performed a MEDLINE literature search and reference review from January 1980 to May 2020 for terms (“mucous fistula re-feeding” or “enteral re-feeding”) and neonates. We in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…On the contrary, Yabe et al cultured the stoma output 3 hours after its ejection and detected no pathogenic bacteria [9]. In a recent review, infection was not described as a MFR-related complication [27]. In our study, stoma contents were collected and recycled every 4 hours.…”
Section: Discussionmentioning
confidence: 66%
“…On the contrary, Yabe et al cultured the stoma output 3 hours after its ejection and detected no pathogenic bacteria [9]. In a recent review, infection was not described as a MFR-related complication [27]. In our study, stoma contents were collected and recycled every 4 hours.…”
Section: Discussionmentioning
confidence: 66%
“…On the contrary, Yabe et al cultured the stoma output 3 h after its ejection and detected no pathogenic bacteria [ 9 ]. In a recent review, infection was not described as a MFR-related complication [ 27 ]. In our study, stoma contents were collected and recycled every 4 h. Two cases of sepsis occurred during MFR, but the relationship between MFR and sepsis could not be determined in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Two previous systematic reviews have been published about its use in neonates: Richardson et al 29 reviewed 5 studies and concluded clinical benefits such as weight gain and reduced use of parenteral nutrition, and the recent review by Ghattaura et al 30 (11 studies) also suggested significant clinical benefits such as better weight gain, shorter duration of parenteral nutrition, lower chance of anastomotic leak and quicker progression to full feeds after reversal. Neither of these studies, however, carried out a meta-analysis of the quantitatively reported outcomes in the literature, and the largest published study on the use of MFR in neonates was published in 202124 after the publication of both these systematic reviews.…”
Section: Discussionmentioning
confidence: 99%